RESPONSE OF MAIZE YIELD, QUALITY AND NITROGEN USE EFFICIENCY INDICES TO DIFFERENT RATES AND APPLICATION TIMINGS - A. Niaz; M. Yaseen; M. Arshad; R. Ahmad (Journal of Animal and Plant Sciences, 2015)
Efficient use of nitrogen by maize warrants screening for an adequate amount to be applied at effective timing which could bring synchronization between N demand and its supply through fertilizer, increasing production and N use efficiency. A 4 × 5 factorial experiment was conducted to assess the effect of variable nitrogen rates and various application timing schemes on yield, quality, and nitrogen use efficiency indices of maize in randomized complete block design with three replications. Four N rates (N1 = 125, N2 = 150, N3 = 175 and N4 = 200 kg N ha-1) were subjected to various timing schemes (S1 = 100% N before planting, S2 = 75% N before planting + 25% N at V9 (9 leaves stage), S3 = 50% N before planting + 50% N at V9, S4 = 25% N before planting + 75% N at V9 and S5 = 100% N top dressed at V9). Results indicated that delaying more than 25% of N rate late up to the V9 stage proved significantly better regarding all the studied parameters while S1 timing scheme was found to be least effective. The treatment combinations N4S3, N4S4 and N3S4 were significantly at par (P>0.05) giving 7.49, 7.34 and 7.12 t ha-1 grain yield, respectively. Treatment N3S4 provided significantly higher (P<0.05) N-partial factor productivity (40.68 kg kg-1) and agronomic-N efficiency (28.22 kg kg-1). Nitrogen rate N4 produced significantly higher (P<0.05)N concentration in stover (0.40%) and total N accumulation (173.86 kg ha-1). Grain N concentration, grain protein concentration, grain oil concentration, N-uptake efficiency, N-physiological efficiency and N-internal utilization efficiency could not be significantly affected by N application rate of N4 above N3. Nitrogen rate N3 gave the highest degree of synchrony between N demand and supply. Nitrogen rates N1 and N2 gave significantly lower results than N3 and N4. It is concluded that split application of N3 through timing scheme S4 could be appropriate one giving higher production, grain quality and N use efficiency.
Keywords: Nrate; application timing; N use efficiency; Synchrony between N demand and supply; maize